ЎҚИТУВЧИ КАСБИЙ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНТИРИШДА ИННОВАЦИОН ТАЪЛИМ МУҲИТИНИНГ ЎРНИ - Бердиева, Ҳ.М. (SCIENCE and SOCIETY, 2020)
The article highlights some aspects of the development of teacher’s pedagogical competence in accordance with innovative educational environment.